2009
DOI: 10.1111/j.1530-0277.2008.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and Alcohol‐Related Harm Among New Zealand University Students: Findings From a National Web‐Based Survey

Abstract: Strategies are needed to reduce the availability and promotion of alcohol on and around university campuses in New Zealand. Given the high prevalence of binge drinking in high school and its strong association with later binge drinking, strategies aimed at youth drinking are also a priority. In universities, high-risk drinkers should be identified and offered intervention early in their undergraduate careers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
131
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 33 publications
14
131
4
3
Order By: Relevance
“…The harm most experienced was a hangover, followed by vomiting, blackouts and emotional outbursts; consistent with other research. 7,15 Of the sexual harms, almost half of students reporting high-risk consumption had experienced unprotected sex, almost 20% experienced a sexual situation they were unhappy with at the time and over a third experienced a sexual situation they later regretted; consistent with past research. 7,15,18 Unprotected sex increases the vulnerability of students to long-term consequences, such as pregnancy and sexually transmitted diseases.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The harm most experienced was a hangover, followed by vomiting, blackouts and emotional outbursts; consistent with other research. 7,15 Of the sexual harms, almost half of students reporting high-risk consumption had experienced unprotected sex, almost 20% experienced a sexual situation they were unhappy with at the time and over a third experienced a sexual situation they later regretted; consistent with past research. 7,15,18 Unprotected sex increases the vulnerability of students to long-term consequences, such as pregnancy and sexually transmitted diseases.…”
Section: Discussionsupporting
confidence: 76%
“…There were no gender differences found for Health and Emotional Harm; past research has found little significant difference for most individual health and emotional harms between genders. 7,15 Students who reported high-risk consumption were significantly more likely to encounter each of the harms listed across the three components compared with those reporting low-risk consumption. The harm most experienced was a hangover, followed by vomiting, blackouts and emotional outbursts; consistent with other research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sampling and recruitment procedures replicated earlier surveys, which have been described previously (Kypri et al 2009). Participants were invited by letter and email to complete the survey, and up to four reminders were sent to nonresponders.…”
Section: Surveymentioning
confidence: 94%